ANALYSIS OF PHOTOCHEMICAL PROFILE AND ENDOSYMBION BIOMASS OF CORAL Symbiodinium sp - Moh Muhaemin; Henky Mayaguezz; Anma Hari Kusuma; Wike Ayu Eka Putri (Jurusan Perikanan dan Kelautan, 2022)
Coral reefs are important ecosystems with the highest species diversity on earth. Besides its high ecological and economic value, it turns out that coral reefs are facing global climate change. One of the environmental factors affected by the effects of global climate change is the penetration of sunlight that reaches the earth's surface. Symbiodinium as a coral endosymbiont turns out to have an adaptation pattern that is correlated with environmental conditions, especially light. The research focused on the interaction between solar radiation and Symbiodinium and its biochemical profiles, which have an important meaning for coral reef ecology and its recovery when affected by excessive light. In addition, it opens up opportunities for the use of light as a triggering factor for the production of certain biochemical compounds in cells. The micro-habitat conditions in the laboratory are made in such a way that it can provide penetration of light intensity that is at the optimal or extreme threshold for Symbiodinium. The measured light intensity is expected to trigger the process of cellular adaptation and the production of certain biochemical compounds in cells. The results are expected to show that light has a significant effect on changes in the content of biochemical compounds in Symbiodinium biomass. The increase in light intensity is expected to guide cells to increase the concentration of lipids and intracellular fibers.